"The conversation has more levels": exploring Zoom's text chat as a discussion mediator in middle school teachers' online professional development. Issue 2 (3rd April 2023) - Nash, Brady L.; Zengilowski, Allison; Schallert, Diane L.
Abstract: This study examined the role of text-based discussions in mediating middle school teachers' discussions during a semester-long, online, synchronous professional development sequence. The PD sequence involved teachers engaged in weekly Zoom meetings, during which they learned about digital literacy and designed curricula. Qualitative data analysis of the transcripts of Zoom chats and spoken comments revealed three central findings: text-based chatting a) provided an additional, public mode for participants to mediate thinking and collaboration, b) allowed for multilayered, democratic, and more equitable access to the conversation, and c) served as an informal space where participants built community through playful discourse. The findings highlight the potential of multimodal, multilayered discussion spaces for facilitating collaborative thinking and more equitable discussion access for learners.